Implementing Gender Mainstreaming in Indonesian Local Government: The Case of Tangerang Regency - Nurdin (Jurnal Transformative)
This research is about the implementation of gender mainstreaming policies in local governments in Indonesia since the enactment of Presidential Instruction No. 9 of 2000 on Gender Mainstreaming in National Development. After running for almost two decades, the implementation of gender mainstreaming has not succeeded in having a significant impact in realizing gender equality in Indonesia in general and Tangerang Regency in particular. Indicators of poverty, domestic violence, and unemployment are still experienced by women. The low index of gender empowerment and women's representation in politics is another indicator that shows the failure of gender mainstreaming in development. Gender inequality in development is caused by internal and external factors that directly impact the achievement of gender equality. Internal factors refer to the low political commitment of regional leaders in initiating the making and stipulation of local regulations on gender mainstreaming in development. Meanwhile, external factors refer to the strong patriarchal culture in Indonesian society which still views women as incapable of political leadership and policy making.